FINANCING AGREEMENT IN THE IMPLEMENTATION OF ONLINE SHOPPING SHOPEEPAY LATER: A Study of Qarḍh Contracts in the Perspective of Islamic Economic Law - Rizkiyanda, Atika (JURISTA: Jurnal Hukum dan Keadilan, 2017)
According to the Fiqh Muamalah concept of debt and credit called qardh, the qardh contract is one of the most dominant alternatives used by the community in conducting business activities. Developments in the field of information technology have now progressed rapidly with the existence of e-commerce, namely online buying and selling or trading transactions. Shopee is one of the marketplaces that is very successful and popular with its users in Indonesia, the problem from the perspective of Islamic law when in financial matters is supplemented by administrative costs, namely the buyer is always charged a 1% handling fee for debts provided by third parties PT. Commerce Finance. In the qardh contract, there is no addition, where when the borrower repays the loan, he is required to add to the principal loan. The formulation of the problem of this research is how is the mechanism of the financing agreement for buying and selling online through ShopeePay Later and what is the review of Fiqh muamalah regarding qardh contracts for financing agreements for buying and selling online through ShopeePay Later. This study uses a type of descriptive qualitative research analysis with data collection techniques through interviews and documentation. The results of the study show that the practice of online shopping using ShopeePay Later has fulfilled the pillars and legal requirements of the debt and credit contract with the existence of a contract sighat, aqid, ma'qud alaih and the purpose of the contract.